Preparation and properties characterization of composite modified starch-based orodispersible films - Yaoyao Zhao, Yuqi Feng, Xiaoqing Ren, Yuru Hou, Fangyuan Wang, Runze Wang, Mintong Guo, (Journal of Applied Pharmaceutical Science, 2024)
Polymer selection is critical in the formulation design of orodispersible films (ODFs). The purpose of this paper is to design and evaluate ODFs based on modified starches, as well as to investigate how polymer types and ratios may affect the performance of the ODFs. To prepare ODFs by solvent casting, modified starches (LYCOAT® RS 720, LYCATAB® DSH, Starch 1500®, and water-soluble starch) were blended with either polyvinyl alcohol or pullulan at different ratios (0:1, 4:1, 1:1, 1:4, 1:0) to enhance the overall film properties. The physicochemical and mechanical evaluations of the formulation were carried out, and solid characterizations were conducted to assess the properties of ODFs. The composite films’ release rate and disintegration pattern vary significantly depending on the polymer types and ratios, which could meet the target drug release profile. Montelukast sodium was selected to prepare the drug-loaded film based on the rationale for ODFs, and the tensile strength and elongation of the drug-loaded films could reach 10.86 MPa and 226.65%, respectively. In vitro dissolution results showed that the drug-loaded films achieved more than 80% drug release within 15 minutes, similar to that of Singulair® chewable tablets. The experimental findings demonstrated that composite films incorporating modified starch exhibited favourable characteristics in terms of morphology, disintegration time, and flexibility. These films hold promise for utilization in ODFs for formulating drugs with diverse release profiles. The incorporation of novel polymer combinations offers opportunities for tailoring drug release patterns to achieve specific therapeutic objectives.
Keywords: Orodispersible films, modified starch, film-forming polymers, dissolution